Introducing the Tri-layered Student Online Experience Framework: Moving from file repository to narrative journey (Journal of Applied Learning and Teaching, 2020)
Online learning environments (OLE) play a vital role in delivering quality learning outcomes. However, despite calls for improved learning environments, the practice of translating traditional face-to-face delivery into quality online offerings remains patchy. OLEs have implications for student experience, and thus student retention. In this paper we examine three domains that shape student experience, ‘relevance of online content’, ‘alignment of online content with student aspirations’, and ‘navigation with the online environment’ and propose that students evaluate online materials based on what they find interesting, and what they deem a value-add investment in exchange for their time. Drawing from the literature, as well as our experience in the field, we present a conceptual framework, the Tri-layered Student Online Experience Framework (TSOEF), which aims to act as a practical resource for academic and education technologists for informing the design of online units. To illustrate how our Framework can be operationalised, we provide an implementation case study centred on a third-year undergraduate unit at the University of Tasmania in Australia. This paper offers a practical guide for providing students with value-driven offerings.